Effect of Time and Intensity of Pruning on Vegetative Growth, Fruit Yield and Quality of Phalsa - Meghwal, P R (Annals of Arid Zone, 2016)
Phalsa (Grewia slibinaeqllalis) is one of the few fruit crops of semi-arid region, which can successfully be grown in hostile climatic condition of arid region with limited supplemental irrigations. Pruning is essential for fruit bearing. Thus, exact time and severity of pruning needs to be standardized under arid conditions. The plants were pruned on three dates viz., 215t December, 3151 December and 10th January at three levels, i.e. 80 cm, 100 cm and 120 cm height from ground level. Pruning time and intensity had significant effect on plant height, number of branches, number of nodes per branch, number of effective nodes, acidity of fruits and fruit yield. Maximum fruit yield (1867 g planf') was obtained by pruning the bushes at 120 cm from ground level on 3151 December, which was significantly higher from rest of treatment combinations of pruning time and intensity. Based on the results of the study, it could be concluded that pruning- in phalsa should be done on 3151 December at 120 cm height from ground level under the agroclimatic conditions of north-western Rajasthan.